Application of Fault Predication and Health Managementin Metro Vehicle Operation and Maintenance - PAN Ying (Kongzhi Yu Xinxi Jishu)
It analyzed the current situation of rail transit and proposed a fault prediction and health management(PHM) method for metro vehicles supported by sensor technology and big data analysis technology. By this technology, functions of centralized monitoring, health assessment and maintenance suggestion of metro vehicles can be realized from three levels: data collection, data analysis and data application. Applications of the PHM technology in the pantograph-catenary monitoring system, the running part monitoring system, the door door system and the central maintenance system of a Shanghai subway were introduced. The results show that the maintenance efficiency of vehicles can be improved by 10% and the cost of whole lifetime operation and maintenance will be reduced by 20%.